Predicting ACL injury using machine learning on data from an extensive screening test battery of 880 female elite athletes - Jauhiainen, S.; Kauppi, J.-P.; Krosshaug, T.; Bahr, R.; Bartsch, J.; Äyrämö, S. (The American Journal of Sports Medicine, 2022)
Background: Injury risk prediction is an emerging field in which more research is needed to recognize the best practices for accurate injury risk assessment. Important issues related to predictive machine learning need to be considered, for example, to avoid overinterpreting the observed prediction performance.